Effect of double boiler heat treatment on the physicochemical properties of sweetened condensed filled milk - Shaziman, S.; Karim, R.; Wan Ibadullah, W.Z.; Mustapha, N.A.; Mohd Adzahan, N. (Rynnye Lyan Resources, 2025)
Sweetened Condensed Filled Milk (SCFM) is a widely used concentrated milk product in Malaysia. While there have been numerous articles on the physicochemical analysis of sweetened condensed filled milk (SCFM), not much research has been done on the effect of heating temperature on its physicochemical properties. This study investigated the impact of heating temperature on the physicochemical properties of SCFM using a 10 L double boiler. SCFM was heated at different temperatures (50°C, 60°C, 70°C, 80°C, and 90°C) and analysed for various properties such as total soluble solids (TSS), pH, carbohydrates (lactose, sucrose, and glucose), colour, water activity, moisture content, particle size analysis, and viscosity. The study found that higher heating temperatures decreased moisture content and increased TSS, protein and viscosity of the SCFM sample. The water activity of SCFM was found to be below 0.85, indicating a low risk of microbial contamination. Increasing the heating temperature significantly (p < 0.05) affected the colour, particle size and carbohydrate content (lactose, sucrose, and glucose) of the SCFM. Based on the analysis, a heating temperature of 70°C for 60 mins was chosen as the most suitable processing parameter for producing SCFM with acceptable physicochemical properties. In conclusion, this study sheds light on the impact of heating temperature on the physicochemical properties of SCFM and provides insights into the optimal conditions for producing SCFM with desirable properties.